2023
DOI: 10.1111/aogs.14514
|View full text |Cite
|
Sign up to set email alerts
|

Use of endoanal ultrasound in detecting obstetric anal sphincter injury immediately after birth

Abstract: Introduction Obstetric anal sphincter injury (OASI) complicates around 5% of deliveries in primiparas. The study objective was to assess the utility of three‐dimensional endoanal ultrasonography (3D‐EAUS) in the diagnosis of OASI. Material and methods The present study was designed to mirror screening settings with an unselected cohort of nulliparous women. All enrolled patients underwent clinical examination of the perineum by the caregiver, and 3D‐EAUS was conducted. Post‐processing of ultrasonography volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This present study formed part of an interdisciplinary project involving birth‐related perineal injuries, endoanal ultrasonography, and postpartum pelvic floor disorders, and was a follow‐up to a cohort of the aforementioned projects 18 . Eligible for study inclusion were primiparous patients who delivered vaginally at >34 weeks during the project period (January 2016–January 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This present study formed part of an interdisciplinary project involving birth‐related perineal injuries, endoanal ultrasonography, and postpartum pelvic floor disorders, and was a follow‐up to a cohort of the aforementioned projects 18 . Eligible for study inclusion were primiparous patients who delivered vaginally at >34 weeks during the project period (January 2016–January 2018).…”
Section: Methodsmentioning
confidence: 99%
“…This present study formed part of an interdisciplinary project involving birth‐related perineal injuries, endoanal ultrasonography, and postpartum pelvic floor disorders, and was a follow‐up to a cohort of the aforementioned projects. 18 Eligible for study inclusion were primiparous patients who delivered vaginally at >34 weeks during the project period (January 2016–January 2018). The study had a prospective cohort design and was conducted in the Department of Obstetrics and Gynecology of Östersund Hospital, where approximately 1300 women deliver each year.…”
Section: Methodsmentioning
confidence: 99%
“…Our research group has explored the rationale that a thin perineal body, represented by a short AVD, means that tissues are stretched or lacking. It has previously been shown that a short/thin perineal body, identified by palpation or transperineal ultrasound after delivery is associated with a higher degree of perineal/anal laceration during vaginal delivery 44,45 . It has been concluded that imaging diagnostics using different ultrasound methods in the acute phase does not add any more information for identifying a rupture in the external sphincter than the manual examination performed by the midwife and the physician 30 .…”
Section: Diagnostics Of Perineal Lacerationsmentioning
confidence: 99%
“…10 There are conflicting studies on the utility of immediate postpartum EAUS to aid initial diagnosis of perineal trauma prior to repair. 11,12 One randomised control trial of 752 women who were randomised to routine examination or immediate EAUS found that EUAS before perineal repair may reduce rates of severe anal incontinence. 13 In contrast, another study reported that nearly 20% of scans performed immediately postpartum were 'non-assessable' due to poor image quality, and were difficult to perform on labour ward due to staff inexperience.…”
mentioning
confidence: 99%